Tumor Necrosis Factor-Alpha Signaling May Contribute to Chronic West Nile Virus Post-infectious Proinflammatory State - Leis, A. Arturo; Grill, Marie F.; Goodman, Brent P.; Sadiq, Syed B.; Sinclair, David J.; Vig, Parminder J. S.; Bai, Fengwei (Frontiers in Medicine, 2020)
Background West Nile virus (WNV) causes a spectrum of human disease ranging from a febrile illness (WNV fever) to severe neuroinvasive disease (meningitis, encephalitis, acute flaccid paralysis). Since WNV gained entry into North America in 1999, clinicians caring for WNV survivors have observed persistent neurological symptoms occurring long-after the production of neutralizing antibodies and clearance of the virus. Accordingly, alternative pathogeneses other than direct viral invasion have been hypothesized to explain these post-infectious symptoms. The dominant hypothesis is that antiviral inflammatory responses triggered initially to clear WNV may persist to promote a post-infectious proinflammatory state. Methods In 4 serologically-confirmed WNV patients with persistent post-infectious symptoms (3 WNV fever, 1 neuroinvasive disease), we ordered a comprehensive cytokine panel at weeks 8, 10, 12 and 36 months post-onset of illness, respectively, to better understand the pathophysiology of the protracted symptoms. Results All patients had abnormally elevated tumor necrosis factor alpha (TNF-α), a major molecule triggering antiviral cytokines and chronic inflammation in many human autoimmune diseases, but heretofore not reported to be upregulated in human WNV infection. Three patients also had elevations of other proinflammatory proteins. Major symptoms included fatigue, arthralgias, myalgias, generalized or multifocal pain or weakness, imbalance, headaches, cognitive problems, and symptoms of dysautonomia. Conclusion The findings provide support for an extended post-infectious proinflammatory state that may contribute to chronic inflammation and long-term morbidity in some WNV survivors and further suggest that TNF-α may play a pathogenic role in initiating this inflammatory environment. Clinical trials are warranted to determine if TNF-α inhibitors or other immunosuppressive agents can improve patient outcomes.